Lupus IgG deposition causes arthritis but inhibits bone destruction through competitive occupation of FcγRI and reduced RANKL signalling. Issue 9 (6th September 2020) - Qiao, Wei; Ding, Huimin; Zuo, Yuyue; Jiang, Lijuan; Zhou, Jiayuan; Han, Xiaoxiao; Yu, Likai; Du, Rong; M Hedrich, Christian; Deng, Guo‐Min
Abstract: Objectives: Bone destruction is a remarkable feature of inflammatory arthritis. It remains unknown why arthritis associated with the systemic autoimmune/inflammatory condition systemic lupus erythematosus (SLE) does not result in erosion and destruction. We aimed to determine the role of autoantibody in the pathogenesis of non‐erosive arthritis in SLE. Methods: We analysed medical record of SLE patients, investigated whether autoantibody induces arthritis lacking bone destruction in animal models and determined whether SLE autoantibody inhibits osteoclastogenesis induced by RANKL in vitro experiments. Results: We found that arthritis lacking bone erosions is common in SLE patients and lupus‐prone mice. Intraarticular injection of lupus serum or IgG induces immune complex deposition and arthritis, but does not result in bone destruction. Deposition of IgG, monocytes/macrophages and TNF‐α is all required for the development of arthritis. Lupus serum or IgG inhibits RANKL‐induced differentiation of monocytes into osteoclast in a dose‐dependent manner. FcγR acts as co‐receptors for RANKL and is involved in osteoclastogenesis. Deficiency of FcγRII or FcγRIII does not affect osteoclastogenesis in the presence of SLE IgG. However, lupus IgG competes for FcγRI binding with RANKL, thereby reducing osteoclastogenesis. Conclusion: Observations from this study demonstrate that IgG from SLE patients can induce arthritis and inhibits RANKL‐induced osteoclastogenesis through competitive occupation of FcγRI on monocytes/macrophages. This study improves the understanding of the pathophysiology of SLE‐associated arthritis and offers a protective mechanism (FcγRI inhibition) that may be targeted in other forms of autoimmune/inflammatory arthritis, such as RA, to prevent or limit bone erosion and inflammatory bone loss. Abstract : In this study, we found that lupus IgG deposition in joints can induce synovial inflammation. Recruitment of lupus IgG to FcγRI may result in functional deficiency of FcγRI on the cellular membrane, which is required for RANKL‐induced osteoclastogenesis. Thus, joint deposited lupus IgG induces arthritis while inhibiting bone erosion.